Congenital Extra-Ventricular (Ganglio)Neurocytoma of the Brain Stem: A Case Report - Piras, Marta; Miele, Evelina; Di Giannatale, Angela; Colafati, Giovanna S.; Diomedi-Camassei, Francesca; Vinci, Maria; de Billy, Emmanuel; Mastronuzzi, Angela; Carai, Andrea (Frontiers in Pediatrics, 2018)
Extraventricular neurocytoma (EVN) is an extremely rare tumor of neuroglial origin with a tendency toward ganglionic or glial differentiation. In the 2016 World Health Organization Classification, EVN was classified as a grade II tumor and described as a neoplasm with good outcome. However, the presence of cellular atypia is an important unfavorable prognostic factor. Here, we describe the first case of a patient with a congenital EVN localized in the brainstem. After a sub-total resection, his disease rapidly progressed despite several chemotherapies, including molecular targeting approaches. He died 13 months after diagnosis. In conclusion, we report an atypical case of EVN presenting an extremely aggressive behavior, despite the absence of cellular atypia. The brainstem origin and the age of the patient may have represented two important prognostic factors for our patient.